2021
DOI: 10.1002/cnr2.1361
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of metabolic enzyme genes associated with leukocyte mitochondrial DNA copy number in PAHs exposure workers

Abstract: Background: Polycyclic aromatic hydrocarbons (PAHs) exposure had been reported to be a risk factor of mtDNAcn in our early study. However, the effect of metabolic enzymes' genetic polymorphisms on mtDNAcn in PAHs-Exposure workers has not been fully evaluated.Aim: The aim of the study was to explore the effect of metabolic enzymes' genetic polymorphisms on mtDNAcn in PAHs-Exposure. Methods and Results:We investigated the effects of metabolic enzymes' genetic polymorphisms on mtDNAcn among 544 coke oven workers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…As reported in our previous research ( 25 ), the results were shown in Table 2 . The effect of gender on mtDNA copy number was statistically significant in the control group but not in the exposed group.…”
Section: Resultssupporting
confidence: 77%
“…As reported in our previous research ( 25 ), the results were shown in Table 2 . The effect of gender on mtDNA copy number was statistically significant in the control group but not in the exposed group.…”
Section: Resultssupporting
confidence: 77%